Active involvement of young people with T1DM during outpatient hospital consultations: Opportunities and challenges in transitional care services. Issue 6 (June 2022) - Peeters, Mariëlle A.C.; de Haan, Hielke G.; Bal, Roland A.; van Staa, AnneLoes; Sattoe, Jane N.T.
Highlights: Involving young people with T1DM actively in care proved to be difficult. Developmental issues often remain unaddressed in transitional diabetes care. Both preferable and non-preferable practices occur in outpatient consultations. Adequate transitional care requires a person-centered approach. Young people's agenda-setting and shared decision-making should be encouraged. Abstract: Objective: Little is known about active involvement of young people (YP) with type 1 diabetes (T1DM) in transitional care. This study aims to gain insight into patient-provider interactions during outpatient hospital consultations. Methods: Semi-structured observations (n = 61) of outpatient consultations with YP with T1DM (15–25 years) treated in 12 hospitals in the Netherlands. The consultations concerned pediatric care (n = 23), adult care (n = 17), and joint consultations (n = 21). Thematic data analysis focused on whether professionals engaged in open, in-depth conversations; used motivational interviewing techniques; involved YP in shared decision-making; and addressed non-medical topics. Results: Apart from some good examples, the healthcare professionals generally had difficulty interacting adequately with YP. They paid little attention to the YP's individual attitudes and priorities regarding disease management; non-medical topics remained generally underexposed. Conversations about daily life often remained shallow, as YP's cues were not taken up. Furthermore, decisions about personal and health-related goals were often not made together. Conclusion: By adopting a more person-centered approach, professionals could empower YP to take an active role in their diabetes management. Practice implications: Using a structured conversation model combined with a tool to encourage YP's agenda-setting and shared decision-making is recommended for more person-centered transitional care in T1DM.